Food protein‐induced enterocolitis syndrome: guidelines summary and practice recommendations. Issue 2 (18th January 2019) - Mehr, Sam; Campbell, Dianne E
Summary: Food protein‐induced enterocolitis syndrome (FPIES) is a poorly understood non‐IgE gastrointestinal‐mediated food allergy that predominantly affects infants and young children. Cells of the innate immune system appear to be activated during an FPIES reaction. Acute FPIES typically presents between one and 4 hours after ingestion of the trigger food, with the principal symptom being profuse vomiting, and is often accompanied by pallor and lethargy. Additional features can include hypotension, hypothermia, diarrhoea, neutrophilia and thrombocytosis. In Australia, the most commonly reported foods responsible for FPIES are (in descending order) rice, cow's milk, egg, oats and chicken. Most children with FPIES react to only one food trigger, and thus, avoidance of multiple foods is often not indicated. FPIES is often misdiagnosed as sepsis or gastroenteritis. However, a diagnosis of FPIES is favoured if there is rapid resolution of symptoms within hours of presentation, an absence of fever, and a lack of a significant rise in C‐reactive protein at presentation. Diagnosis is often hampered by the lack of awareness of FPIES, absence of reliable biomarkers, the non‐specific nature of the presenting symptoms, and the delay between allergen exposure and symptoms. Although some national peak allergy bodies have attempted to improve the diagnosis and management of FPIES, up until 2017 there were no internationally agreed guidelines for its diagnosis and management.